2021
DOI: 10.15252/embj.2021109575
|View full text |Cite
|
Sign up to set email alerts
|

AMPK CA(R)Sts a new light on amino acid sensing

Abstract: AMP‐activated protein kinase (AMPK) is recognized as a critical regulator of cellular energy metabolism impacted by AMP/ATP and ADP/ATP ratios, or glucose‐ and fatty acid‐derived metabolites. However, its ability to sense alterations in amino acid levels is poorly understood. Recent work by Yuan et al (2021) identifies a novel mechanism of AMPK regulation responsive to changes in availability of the sulfur‐containing amino acid cysteine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Cellular bioenergetics deficiency is a critical trigger for autophagy induction [45][46] . The elevation of AMP/ATP ratio in cells activates cellular energetic sensor, AMPK, leading to the suppression of anabolism and promotion of catabolism [47][48][49][50] . We identified that eBAG treatment depleted cellular bioenergetics and resulted in AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular bioenergetics deficiency is a critical trigger for autophagy induction [45][46] . The elevation of AMP/ATP ratio in cells activates cellular energetic sensor, AMPK, leading to the suppression of anabolism and promotion of catabolism [47][48][49][50] . We identified that eBAG treatment depleted cellular bioenergetics and resulted in AMPK activation.…”
Section: Discussionmentioning
confidence: 99%